Application of Moist Wound Healing with Hydrogel on Diabetic Wounds at Asri Wound Care Center Medan - Rafika Nur Siregar; Fajar Ari Gemilang (Universitas Prima Indonesia, 2026)
Diabetic foot ulcer is a common and serious complication of diabetes mellitus that requires effective wound management to accelerate healing and prevent further complications. Objective: This study aimed to evaluate the effectiveness of moist wound healing using hydrogel in improving wound healing outcomes among patients with diabetic foot ulcers at Asri Wound Care Center Medan. Methods: This study employed a case study design with purposive sampling. A total of five patients with diabetic foot ulcers stage 4 were included, consisting of three patients in the treatment group and two patients in the control group. Wound healing outcomes were assessed using the Bates-Jensen Wound Assessment Tool (BWAT) over seven wound care sessions. Results: The treatment group demonstrated a more significant improvement in wound healing compared to the control group. BWAT scores in the treatment group decreased from 43 to 24 (R1), 40 to 20 (R2), and 39 to 20 (R3), indicating marked reductions in necrotic tissue, slough, biofilm, and exudate, along with improved wound base and granulation tissue formation. In contrast, the control group showed smaller reductions in BWAT scores, from 40 to 34 (R4) and 41 to 33 (R5), reflecting a slower healing process with residual necrotic tissue and exudate. Conclusion: Moist wound healing using hydrogel was more effective than conventional wound care in accelerating the healing of diabetic foot ulcers, as evidenced by greater BWAT score reductions and improved wound characteristics. These findings support the use of hydrogel as an effective dressing in diabetic wound management.